Frailty and kidney transplant candidates - María José Pérez-Sáez; Álex Gutiérrez-Dalmau; Francesc Moreso; Leocadio Rodríguez-Mañas; Julio Pascual (Nefrología (English Edition), 2021)
Frailty is a concept that has been mainly developed in geriatrics and it came from the need of identifying subjects at risk to develop complications when they faced a stressful event. Frail patients have higher risk of mortality, poor outcomes and disability, and this is independent from their age or comorbidities. Chronic kidney disease patients present with high prevalence of frailty, especially those who are in renal replacement therapy. Frail or pre-frail patients on the kidney transplant waiting list represent 20–30%, and these patients are proven to have poorer results after the transplant, which is a stressful event itself. Tools for frailty assessment, both scales or indexes, may be useful to identify which subjects might be at risk for complications after transplant, and this is necessary to adapt our clinical practice and minimize morbidity. The most used frailty scale in kidney patients is Fried scale, which is based in five phenotypic items. Besides that, knowing frail population allows potential interventions such as prehabilitation while the patient is waiting for the kidney transplant, which the aim of improving their vulnerability prior to transplant and, therefore, optimizing results after transplant. More studies are needed amongst kidney patients to improve and prevent frailty. Resumen: El concepto de fragilidad ha sido desarrollado principalmente en el campo de la geriatría y surgió para identificar a aquellos pacientes que presentaban vulnerabilidad al enfrentarse a un evento clínico estresante. Los pacientes frágiles tienen mayor riesgo de mortalidad, complicaciones y discapacidad, independientemente de su edad o comorbilidades. Se ha descrito una alta prevalencia de fragilidad entre sujetos con enfermedad renal crónica, sobre todo en terapia renal sustitutiva. El porcentaje de pacientes frágiles o prefrágiles en lista de espera de trasplante renal se sitúa en torno a un 20–30% y se ha demostrado que estos pacientes tienen peores resultados tras el trasplante renal, que constituye un evento estresante. Las herramientas para evaluar la fragilidad, escalas e índices, pueden ser útiles para identificar qué pacientes están en riesgo de padecer más complicaciones postrasplante, lo que resulta necesario para adaptar nuestra práctica clínica y evitar morbilidad. La más utilizada en pacientes renales es la escala de Fried, que se basa en la detección de cinco dimensiones fenotípicas. Además, conocer la fragilidad de nuestros pacientes permite plantear intervenciones prehabilitadoras durante el tiempo que estén en lista de espera, con el objetivo de mejorar esta vulnerabilidad pretrasplante, y así optimizar los resultados postrasplante. Se necesitan estudios en población renal para mejorar y prevenir la fragilidad.